Future challenges and opportunities in language testing and assessment: Basic questions and principles at the forefront. (January 2023) - Brunfaut, Tineke
In this invited Viewpoint on the occasion of the 40th anniversary of the journal Language Testing, I argue that at the core of future challenges and opportunities for the field—both in scholarly and operational respects—remain basic questions and principles in language testing and assessment. Despite the high levels of sophistication of issues looked into, and methodological and operational solutions found, outstanding concerns still amount to: what are we testing, how are we testing, and why are we testing? Guided by these questions, I call for more thorough and adequate language use domain definitions (and a suitable broadening of research and testing methodologies to determine these), more comprehensive operationalizations of these domain definitions (especially in the context of technology in language testing), and deeper considerations of test purposes/uses and of their connections with domain definitions. To achieve this, I maintain that the field needs to continue investing in the topics of validation, ethics, and language assessment literacy, and engaging with broader fields of enquiry such as (applied) linguistics. I also encourage a more synthetic look at the existing knowledge base in order to build on this, and further diversification of voices in language testing and assessment research and practice.